IMPLEMENTASI NILAI-NILAI NKRI DALAM PEMBENTUKAN KARAKTER GENERASI MUDA - Tristan Khalif Zulkarnain (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the implementation of the values of the Unitary State of the Republic of Indonesia (NKRI) in character formation for the younger generation in the digital era. The background of this research is the phenomenon of declining morality and national spirit among adolescents due to the influence of globalization and the development of information technology. The research method used is descriptive qualitative, with a literature review approach from various relevant scientific sources. The results indicate that the values of the Unitary State of the Republic of Indonesia (NKRI), such as diversity, Pancasila, the legal basis and the constitution, are still relevant and can serve as a basis for strengthening the character of the younger generation through formal and non-formal education. The conclusion of this study is that the internalization of the values of the Unitary State of the Republic of Indonesia (NKRI) needs to be carried out continuously with the support of families, schools, and the community to create a generation with strong character, nationalism, and noble morals.